Selective Catalytic Performances of Noble Metal Nanoparticle@MOF Composites: The Concomitant Effect of Aperture Size and Structural Flexibility of MOF Matrices. Issue 47 (27th July 2017) - Chen, Luning; Zhan, Wenwen; Fang, Huihuang; Cao, Zhenmin; Yuan, Chaofan; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract: Noble metal nanoparticles embedded in metal–organic frameworks (MOFs) are composite catalysts with enhanced or novel properties compared to the pristine counterparts. In recent years, to determine the role of MOFs during catalytic process, most studies have focussed on the confinement effect of MOFs, but ignored the structural flexibility of MOFs. In this study, we use two composite catalysts, Pt@ZIF‐8 [Zn(mIM)2, mIM=2‐methyl imidazole] with flexible structure and Pt@ZIF‐71 [Zn(DClIM)2, DClIM=4, 5‐dichloroimidazole] with rigid structure, and hydrogenation of cinnamaldehyde as model reaction, to show the confinement effect and the structure flexibility of MOF matrices on the catalytic performance of composite catalysts. Both catalysts showed high selectivity for cinnamic alcohol with the confinement effect of the aperture. But, compared to Pt@ZIF‐71, Pt@ZIF‐8 exhibited higher conversion but lower selectivity owing to the flexible structure. The above results remind us that we will have to consider both the aperture size of MOFs and structure flexibility to select the proper MOF matrices for the composite materials to achieve the optimized performance. Abstract : Going through the motions : Two composite catalysts (Pt@ZIF‐8 and Pt@ZIF‐71) were designed and synthesized to investigate the concomitant effect of aperture size and structural flexibility of metal–organic framework matrices in catalysis. Compared to the Pt NPs sheathed with the rigid MOFs (Pt@ZIF‐71), the Pt@ZIF‐8 composite catalyst exhibited higher conversion but lower selectivity owing to the flexible structure of ZIF‐8 matrices.